1997
DOI: 10.1175/1520-0442(1997)010<1393:cahcit>2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Climatic and Hydrologic Changes in the Tien Shan, Central Asia

Abstract: The authors analyze climatic and hydrologic data from 110 sites collected from the middle of the twentieth century to the present in the Tien Shan, one of the largest mountain systems of central Asia. In spite of a few confounding interregional variations in the temporal changes of surface air temperature, precipitation, runoff, glacier mass, and snow thickness in the Tien Shan, it has been possible to establish statistically significant longterm trends in these key hydroclimatic variables. The average rise in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

17
232
1

Year Published

2000
2000
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 332 publications
(262 citation statements)
references
References 24 publications
17
232
1
Order By: Relevance
“…Recent concerns about regional climate change have focused attention on the dependence of climate variables on elevation (Beniston and Rebetez 1996;Aizen et al 1997;Shrestha et al 1999;Liu and Chen 2000;Marchenko 1999;Giese and Moβig 2004;Bolch 2007). As far as the increasing rates of dependence of temperature on elevation is concerned, there are many contrasting results in the different mountainous regions.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent concerns about regional climate change have focused attention on the dependence of climate variables on elevation (Beniston and Rebetez 1996;Aizen et al 1997;Shrestha et al 1999;Liu and Chen 2000;Marchenko 1999;Giese and Moβig 2004;Bolch 2007). As far as the increasing rates of dependence of temperature on elevation is concerned, there are many contrasting results in the different mountainous regions.…”
Section: Discussionmentioning
confidence: 99%
“…As far as the increasing rates of dependence of temperature on elevation is concerned, there are many contrasting results in the different mountainous regions. In some mountainous regions, there is increased warming with increasing elevation (Beniston and Rebetez 1996;Aizen et al 1997;Shrestha et al 1999;Liu and Chen 2000). In contrast, some studies have shown that the rates of increase in temperature in the high elevation regions are lower than those in the low elevation regions (Marchenko 1999;Giese and Moβig 2004;Bolch 2007).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lake water temperature ranges between ~16°C in summer and 0-2°C in winter (ice cover usually between October and late April) with almost no vertical variations (<2°C) throughout the water column ( Figure 2b and c). The precipitation regime in the Kyrgyz Tian Shan is presently mainly controlled by the interaction between the Siberian Anticyclone and the mid-latitude Westerlies (Aizen et al, 1997), the latter bringing moisture from the Aral-Caspian Basin, the Mediterranean, the Black Sea, and the North Atlantic (Aizen et al, 2006). In contrast, the Asian summer monsoon does not directly influence the region at present and most likely had only negligible impact since the Mid-Holocene (Cheng et al, 2012).…”
Section: Study Sitementioning
confidence: 99%
“…The predominant wind directions today are from the west and result from the Westerly Jet Stream (Yang et al, 2013) but these are affected by seasonal influences from southern monsoon currents (Cour et al, 1999). The principal factor determining the climatic regimes of the Tian Shan Mountains is the interaction between the southwestern branch of the Siberian anticyclonic circulation and cyclonic activity from the west (Aizen et al, 1997). The high elevation is the main factor influencing the air temperature distribution at a macro scale (Mathis et al, 2014).…”
Section: Study Sitementioning
confidence: 99%